2016
DOI: 10.1039/c6fo00689b
|View full text |Cite
|
Sign up to set email alerts
|

Cajanus cajan – a source of PPARγ activators leading to anti-inflammatory and cytotoxic effects

Abstract: Cajanus cajan is an important legume crop in the human diet in many parts of the world. Due to its pharmacological properties, C. cajan is, moreover, used in traditional medicine for treating skin diseases, diabetes, inflammatory disorders and various other dysfunctions. In this study, we focused on the role of peroxisome proliferator-activated receptor gamma (PPARγ) as a potential therapeutic target of Cajanus cajan and its main compounds for the treatment of cancer, inflammation and inflammation-related diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 31 publications
3
9
0
1
Order By: Relevance
“…13 C‐NMR (CDCl 3 , δ /ppm): 175.83 (‐COOH), 162.47 (C‐2), 162.32 (C‐4), 141.96 (C‐6), 137.31 (C‐1′), 131.97 (C‐C), 130.85 (C‐G), 130.39 (C‐F), 128.77 (C‐3′, 5′), 127.90 (C‐4′), 126.83 (C‐2′, 6′), 121.93 (C‐B), 116.80 (C‐3), 103.36 (C‐5), 103.08 (C‐1), 55.75 (‐OCH 3 ), 25.84 (C‐E), 22.12 (C‐A), 17.82 (C‐D). The above results were consistent with the literature and the compound was identified as cajaninstilbene acid.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…13 C‐NMR (CDCl 3 , δ /ppm): 175.83 (‐COOH), 162.47 (C‐2), 162.32 (C‐4), 141.96 (C‐6), 137.31 (C‐1′), 131.97 (C‐C), 130.85 (C‐G), 130.39 (C‐F), 128.77 (C‐3′, 5′), 127.90 (C‐4′), 126.83 (C‐2′, 6′), 121.93 (C‐B), 116.80 (C‐3), 103.36 (C‐5), 103.08 (C‐1), 55.75 (‐OCH 3 ), 25.84 (C‐E), 22.12 (C‐A), 17.82 (C‐D). The above results were consistent with the literature and the compound was identified as cajaninstilbene acid.…”
Section: Resultssupporting
confidence: 92%
“…13 C‐NMR (CDCl 3 , δ /ppm): 161.14 (C‐3), 156.86 (C‐1), 139.71 (C‐5), 137.07 (C‐1′), 129.42 (C‐4′), 128.71 (C‐3′, 5′), 128.32 (C‐A), 127.80 (C‐B), 126.60 (C‐2′, 6′), 105.94 (C‐6), 104.95 (C‐4), 101.00 (C‐2), 55.40 (‐OCH 3 ). The above results were consistent with the literature and the compound was identified as 3‐methoxy‐5‐(2‐phenylethenyl)‐phenol.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Generally, flavone C‐ glycosides are structural analogues of natural estrogen and are thought to function like selective estrogen receptor modulators and therefore have anticancer effects against hormone‐related cancers. Vitexin and isovitexin have cytotoxic effects on breast (MCF‐7), prostate (PCO‐3), cervix (HeLa), and ovarian cancer (OVCAR) cells by inducing apoptosis via cleavage of PARP, upregulation of Bax, and downregulation of Bcl‐2 . This stimulation of apoptosis seems to be mediated by activation of caspases.…”
Section: Ovary Cervix and Prostate Cancersmentioning
confidence: 99%
“…Cajaninstilbene acid (CSA), a main bioactive stilbene from pigeon pea [ Cajanus cajan (L.) Millsp.] leaves, possesses many bioactivities, including anti-bacterial (Kong et al, 2010), anti-tumor (Fu et al, 2015), anti-osteoporosis (Sun et al, 2019), anti-oxidative (Wu et al, 2011), anti-inflammatory (Patel and Bhutani, 2014; Huang et al, 2016; Schuster et al, 2016), and neuroprotective (Jiang et al, 2014; Liu et al, 2014a) effects. It is reported that stilbenes containing extract-fraction from Cajanus cajan (L.) leaves (sECC) ameliorated Aβ 25–35 -induced cognitive impairment (Ruan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%